Hash-chain-based authentication for IoT - Pinto, Antonio; Costa, Ricardo (Advances in distributed computing and artificial intelligence journal, 2016)
The number of everyday interconnected devices continues to increase and constitute the Internet of Things (IoT). Things are small computers equipped with sensors and wireless communications capabilities that are driven by energy constraints, since they use batteries and may be required to operate over long periods of time. The majority of these devices perform data collection. The collected data is stored on-line using web-services that, sometimes, operate without any special considerations regarding security and privacy. The current work proposes a modified hash-chain authentication mechanism that, with the help of a smartphone, can authenticate each interaction of the devices with a REST web-service using One Time Passwords (OTP) while using open wireless networks. Moreover, the proposed authentication mechanism adheres to the stateless, HTTP-like behavior expected of REST web-services, even allowing the caching of server authentication replies within a predefined time window. No other known web-service authentication mechanism operates in such manner.